Bolstering human capital management and engagement in the health sectors - Adewale Osibanjo; Anthonia Adenike Adeniji; Odunayo Salau; Tolulope Atolagbe; Abisola Osoko; Ogheneofejiro Edewor; Julia Olowu (Cogent Business & Management, 2020)
The health sector is one of the cornerstones and most viable tool for sustainable development. The quest for improved performance has developed momentum over the past years, and this has increased the demand for excellent service. Still, surprisingly the process and array of complexities in employees' selection, education, as well as their career development in the health sector is worrisome with heightened attrition rate. Hence, this paper examines how holistic human capital management is nurtured, implemented and practiced in Nigeria's health sector. The human capital and social exchange theories were also used to explain the issues. The study adopts a cross-sectional approach and descriptive research design to establish trends related to the objectives of this study. A quantitative approach was employed using a modified survey questionnaire in purposively sampling 408 selected health workers in the south-west, Nigeria. The use of measurement model and structural equation modelling (SEM_PLS) was adopted to establish the convergent reliability, model-fit and degree of association. The results established that human capital management dimensions (training and development, mentoring, employee relations, coaching, job design and career development) are significant predictors of employee engagement. Surprisingly, career development and mentoring had the least values. The study concluded by providing a quite detailed analysis of the assumptions underpinning holistic human capital management in Nigeria's health sector and also putting forth viable and pragmatic recommendations.
Keywords: 650; human capital; management; health sector; engagemen